P0816CLINICAL CHARACTERISTICS AND EGFR AND UACR DISTRIBUTION ACCORDING TO THE 2012 KDIGO CKD CLASSIFICATION: A REPORT FROM THE US DISCOVER CKD COHORT. (6th June 2020) - Garcia Sanchez, Juan Jose; Carrero, Juan Jesus; Kumar, Supriya; Pecoits-Filho, Roberto; James, Glen; Lambers Heerspink, Hiddo; Nolan, Stephen; Lam, Carolyn; Chen, Tony; Kanda, Eiichiro; Kashihara, Naoki; Kosiborod, Mikhail; et al.
Abstract: Background and Aims: In 2012, the Kidney Disease Improving Global Outcomes (KDIGO) guidelines recommended categorising and prognosticating chronic kidney disease (CKD) based on estimated glomerular filtration rate (eGFR) and urine albumin to creatinine ratio (UACR). Contemporary studies describing the prevalence and characteristics of patients with CKD categorised according KDIGO 2012 and how studies of new pharmacotherapies relate to these categories are scarce. One such new therapy class of key interest are the sodium glucose co-transporter 2 inhibitors (SGLT-2i), shown to delay the progression to renal failure and prevent cardiovascular/renal death in patients with CKD. We aimed to describe patient characteristics and the prevalence of CKD according to the 2012 KDIGO categories in a large real-world US cohort of patients with CKD (part A). We also describe a subset of the population according to the DAPA-CKD trial inclusion criteria (eGFR [25-75ml/min/1.73m 2 ] and UACR [200-5000mg/g]) (part B). Method: DISCOVER-CKD is an international observational study in patients with CKD. The DISCOVER-CKD retrospective US cohort of patients was extracted using real-world data from the integrated Limited Claims and Electronic Health Record data (IBM Health, Armonk, NY) and HealthVerity. Patients were aged ≥18 years, with ≥1 UACR measure. For part A, required first diagnostic code of CKD (Stages 3A, 3B, 4, 5, or ESRD) or two eGFR of <75 mL/min/1.73 m 2 recorded at least 90 days apart and for part B, two measures of eGFR 25-75 mL/min/1.73 m 2 recorded at least 90 days apart between 1 st January 2008 and September 2018. Index date was diagnostic code or 2nd eGFR. The first UACR, recorded +/-12 months of index, was used to categorise patients. Descriptive analyses were used to summarise prevalence and patient characteristics. Results: Of the overall study cohort (N=4330, 49.1% women, mean age 65.3±10.64 years), by KDIGO categories (part A): 85.7% (n=3601) had normal to mildly increased albuminuria, 11.0% (n=463) had moderately increased albuminuria and 3.3% (n=137) had severely increased albuminuria (Figure 1). 4.6% (n=193) fulfilled DAPA-CKD trial inclusion criteria (part B). In both populations, the most common comorbidities were hypertension (HTN, 73.0% for both) and type 2 diabetes (T2D, 57.6% and 56.2%, respectively). Anti-hypertensive drugs were frequently used (76.4% and 76.9%, respectively). Conclusion: This study, utilising real-world data, adds to the scarcity of knowledge reporting the characteristics of patients with CKD in different eGFR and UACR strata according to the KDIGO 2012 definitions. We observed a trend in higher UACR in the group of patients with lower eGFR and report a high prevalence of T2D and HTN in the study population, demonstrating the high co-morbidity burden in patients, for whom new therapies may be beneficial.